Field Exploitation of Multiple Functions of Beneficial Microorganisms for Plant Nutrition and Protection: Real Possibility or Just a Hope? - Kowalska, Jolanta; Tyburski, Józef; Matysiak, Kinga; Tylkowski, Bartosz; Malusá, Eligio (Frontiers in Microbiology, 2020)
Bioproducts, i.e. microbial based pesticides or fertilizers (biopesticides and biofertilizers), should be expected to play an ever-increasing role and application in agricultural practices world-wide in the effort to implement policies concerned with sustainable agriculture. However, several microbial strains have proven the capacity to augment plant productivity by enhancing crop nutrition and functioning as biopesticides, or vice-versa. This multifunctionality is an issue that is still not included as a concept and possibility in any legal provision regarding the placing on the market of bioproducts, and indicates difficulties in clearly classifying the purpose of their suitability. In this review, we overview the current understanding of the mechanisms in plant-microbe interactions underlining the dual function of microbial strains toward plant nutrition and protection. The prospects of market development for multifunctional bioproducts are then considered in view of the current regulatory approach in the European Union, in an effort that wants to stimulate a wider adoption of the new knowledge on the role played by microorganisms in crop production.